2017
DOI: 10.1111/exd.13373
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and other factors in the aetiology of female pattern hair loss

Abstract: Pattern hair loss is the most common form of hair loss in both women and men. Male pattern hair loss, also termed male androgenetic alopecia (M-AGA), is an androgendependent trait that is predominantly genetically determined. Androgen-mediated mechanisms are probably involved in female pattern hair loss (FPHL) in some women but the evidence is less strong than in M-AGA; other non-androgenic pathways, including environmental influences, may contribute to the aetiology. Genome-wide association studies have ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 95 publications
(108 reference statements)
1
61
0
3
Order By: Relevance
“…The temporal scalp may also be affected like the frontoparietal area in FPHL because of their same embryologic background . Our study has significant implications for clarifying the correlation of each sites’ hair loss, though previous studies have suggested the possibility of hair loss in the occipitotemporal area …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The temporal scalp may also be affected like the frontoparietal area in FPHL because of their same embryologic background . Our study has significant implications for clarifying the correlation of each sites’ hair loss, though previous studies have suggested the possibility of hair loss in the occipitotemporal area …”
Section: Discussionmentioning
confidence: 74%
“…13 Our study has significant implications for clarifying the correlation of each sites' hair loss, though previous studies have suggested the possibility of hair loss in the occipitotemporal area. 4,5,[14][15][16][17][18][19] We used the BASP classification, which has been proposed as a new method for evaluating PHL of male and female patients. 9 BASP classification assesses the involvement area by four basic types (L, M, C and U) and two special types (V and F).…”
Section: Discussionmentioning
confidence: 99%
“…is is unlike the case in patients suffering from male AGA or female pattern hair loss (FPHL), in whom hair density and hair diameter decrease differently. Multiple studies suggest that male AGA is caused by numerous polymorphisms associated with androgen-related genes, while FPHL may have a different etiology and may not be linked to a hormone-driven mechanism [24].…”
Section: Discussionmentioning
confidence: 99%
“…The changeable level of testosterone might exert some roles in the formation of androgenetic alopecia. In addition, no causative variants in CYP17, SRD5A1, SRD5A2, and HR genes associated with alopecia were found by the exome sequencing in this family [16]. Although the hair loss was not specific for AMN, it should be borne in mind that recognition of such an association between alopecia and ABCD1 mutations would likely aid the diagnosis of AMN.…”
Section: Discussionmentioning
confidence: 71%